2017
DOI: 10.1088/1674-4926/38/6/063003
|View full text |Cite
|
Sign up to set email alerts
|

A simple chemical route to synthesize the umangite phase of copper selenide (Cu3Se2) thin film at room temperature

Abstract: Copper selenide (Cu3Se2) thin films have been synthesized with Se as the precursor in aqueous solution by chemical bath deposition technique at room temperature. We have investigated the influence of the growth time ranging from 30 to 90 min on structural, optical and electrical properties of Cu3Se2 thin films. The as-grown film at 60 min exhibits a tetragonal structure and is (101) oriented. The maximum value of crystal size D = 55 nm is attained for Cu3Se2 films grown at 60 min. The Raman spectrum reveals a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Both the WZ and ZB spectra have a major peak at ∼260 cm –1 and one less intense peak at ∼193 cm –1 . In previous research, for Cu 3 Se 2 and Cu 2 Se reference spectra, , the major peak occurs at ∼260 cm –1 , with a less intense peak at ∼190 cm –1 . ZnSe reference spectra have been reported with two major peaks at ∼200 cm –1 (the less intense longitudinal optical phonon mode, LO –1 ) and ∼260 cm –1 (the transverse optical phonon mode, TO).…”
Section: Resultsmentioning
confidence: 72%
“…Both the WZ and ZB spectra have a major peak at ∼260 cm –1 and one less intense peak at ∼193 cm –1 . In previous research, for Cu 3 Se 2 and Cu 2 Se reference spectra, , the major peak occurs at ∼260 cm –1 , with a less intense peak at ∼190 cm –1 . ZnSe reference spectra have been reported with two major peaks at ∼200 cm –1 (the less intense longitudinal optical phonon mode, LO –1 ) and ∼260 cm –1 (the transverse optical phonon mode, TO).…”
Section: Resultsmentioning
confidence: 72%
“…This includes cubic, hexagonal, orthorhombic, monoclinic and tetragonal. Their formation depend upon method of preparation [6,7] and growth conditions. Reports have shown that CuSe mostly possessed hexagonal structural phase at room temperature and go through phase transition to orthorhombic at 48 °C and back to hexagonal phase at 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Copper selenide has been studied with great interest during the past decades because of its potential application in the fabrication of photovoltaic devices [4][5][6][7][8]. It has many phases and structural forms: stoichiometric α-Cu2Se, Cu3Se2, CuSe and CuSe2, as well as non-stoichiometric, Cu2-xSe [9], Cu3Se2 [10][11][12], Cu2-xSe [13], CuSe [14] and Cu2Se [15][16]…”
Section: Introductionmentioning
confidence: 99%